Skin‐Inspired Antibacterial Conductive Hydrogels for Epidermal Sensors and Diabetic Foot Wound Dressings. (4th June 2019) - Zhao, Yue; Li, Zuhao; Song, Shanliang; Yang, Kerong; Liu, Hou; Yang, Zhe; Wang, Jincheng; Yang, Bai; Lin, Quan
Abstract: Recently, artificial intelligence research has driven the development of stretchable and flexible electronic systems. Conductive hydrogels are a class of soft electronic materials that have emerging applications in wearable and implantable biomedical devices. However, current conductive hydrogels possess fundamental limitations in terms of their antibacterial performance and a mechanical mismatch with human tissues, which severely limits their applications in biological interfaces. Here, inspired by animal skin, a conductive hydrogel is fabricated from a supramolecular assembly of polydopamine decorated silver nanoparticles (PDA@Ag NPs), polyaniline, and polyvinyl alcohol, namely PDA@Ag NPs/CPHs. The resultant hydrogel has many desirable features, such as tunable mechanical and electrochemical properties, eye‐catching processability, good self‐healing ability as well as repeatable adhesiveness. Remarkably, PDA@Ag NPs/CPHs exhibit broad antibacterial activity against Gram‐negative and Gram‐positive bacteria. The potential application of this versatile hydrogel is demonstrated by monitoring large‐scale movements of the human body in real time. In addition, PDA@Ag NPs/CPHs have a significant therapeutic effect on diabetic foot wounds by promoting angiogenesis, accelerating collagen deposition, inhibiting bacterial growth, and controlling wound infection. To the best of the authors' knowledge, this is the first time that conductive hydrogels with antibacterial ability are developed for use as epidermal sensors and diabetic foot wound dressing. Abstract : Inspired by the multiple functions of animal skin, a conductive hydrogel is fabricated based on a supramolecular assembly of polydopamine decorated silver nanoparticles (PDA@Ag NPs), polyaniline, and polyvinyl alcohol, namely PDA@Ag NPs/CPHs. The resultant hydrogel has many desirable features, such as tunable mechanical and electrochemical properties, eye‐catching processability, good self‐healing ability as well as repeatable adhesiveness.